Streptomyces palmae CMU-AB204T, an antifungal producing-actinomycete, as a potential biocontrol agent to protect palm oil producing trees from basal stem rot disease fungus, Ganoderma boninense - Kanaporn Sujarit (2020)
© 2020 Elsevier Inc. Palm oil has high economic value in Southeast Asia as a primary source of vegetable oil and in biofuel production. The plant is frequently damaged from the fungal infection of Ganoderma boninense, causing basal stem rot (BSR) disease. This pathological problem results in significant yield loss and death of oil palm trees. The present study aims to develop actinomycetes as inoculants and to evaluate their ability to control this disease. Streptomyces noursei CMU-AB21, Streptomyces sioyaensis CMU-AB83, and Streptomyces palmae CMU-AB204T exhibited the strongest degree of anti-Ganoderma activity in vitro and were chosen as potential biocontrol agents. The actinomycetes were encapsulated in 2% (w/v) sodium alginate at an initial concentration of 109 cfu mL−1. The efficiency of these actinomycetes on the in vivo suppression of BSR was evaluated in oil palm seedlings using spore immobilized alginate beads and free-spore suspension. The most effective inoculant, S. palmae CMU-AB204T, revealed the lowest severity of foliar symptoms (SFS) at 3.7% and 4.5%, and reduced the percentage of disease severity by 81.6% and 75.8% when applied as free-spores and spores encapsulating alginate beads, respectively. Moreover, the seedlings treated with S. palmae CMU-AB204T had the highest degree of plant vigor based on stem diameter and biomass. The bioactive metabolites of this strain were isolated from broth extracts by column chromatography. Mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectra indicated that the compounds produced by S. palmae CMU-AB204T were actinopyrone A (1), anguinomycin A (2) and leptomycin A (3), which revealed inhibitory activity towards G. boninense at 50, 5 and 1.5 µg disk−1, respectively. Based on this evidence, S. palmae CMU-AB204T is a promising candidate in the development of a biocontrol agent that would protect oil palm trees from BSR disease.